POTENSIAL FRAUDULENT FINANCIAL REPORTING: PENGARUH INTERNAL CONTROL DAN TRANSFORMASI DIGITAL DALAM MEMODERASI - Nurhayati, Eva; Susetyo, Dwinanto Priyo (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of internal control on potensial fraudulent financial reporting with digital transformation acting as a moderating variable. The focus of this research is automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2023. This research is quantitative research with an associative descriptive approach. The data used in this study were obtained from the company’s annual financial statements available through The Indonesia Capital Market Institute (TICMI) and analyzed using the help of SPSS 25. The results showed that internal control had no significant effect on potensial fraudulent financial reporting, and digital transformation did not moderate the relationship. These findings make an important contribution to the understanding of the influence of internal control and digital transformation in the context of preventing fraudulent financial reporting in manufacturing companies, especially in the automotive sub-sector listed on the IDX.